SIAK, RIAU AND TERENGGANU, MALAYSIA: The Genetic Relation of the Malay Archipelago Diaspora - Ellya Roza; Taufik Eka Osvi Arrahim; Violeta Inayah Pama (Asia-Pacific Journal on Religion and Society, 2022)
This paper aims to analyze the genetic ties of Siak and Terengganu, Malaysia as a Malay Diaspora group in the archipelago that once outperformed the world in its time, especially in the trade economy. This article is the result of a research library where the search for data does not need to go to the field, but simply by analyzing various sources, both primary and secondary which ultimately results in interpretation as the implementation of content analysis. As for the results of the analysis of various data sources, it is no secret that the Malay diaspora is the dominant group in the archipelago even though the Malay Kingdom of Melaka fell to the Portuguese in 1511 and the Malay Kingdom of Johor has also experienced a throne crisis since the death of Sultan Mahmud Shah II in 1699. This situation Raja Kecil took the opportunity by controlling Johor so he was crowned the 12th Sultan of Johor with the title Sultan Abdul Jalil Rahmat Syah. Meanwhile, the former Sultan of Johor fled to Terengganu to live with his majesty Tun Zainal Abidin (the first Sultan of Terengganu). It means that the king is the father of Tengku Kamariah, the wife of Raja Kecil, who founded the Siak Kingdom in 1723. Then after the death of Sultan Sulaiman, Sultan Mansur returned to Terengganu. In 1761, Treasurer Tun Hassan of Johor and Sultan Ismail of Siak sent letters to Sultan Mansur Terengganu asking for help against the Bugis in Riau. Sultan Terengganu agreed to help them but before the war in 1763 Sultan Ismail had married Tengku Tipah, daughter of Sultan Mansur Terengganu. This means that there is a relationship between Siak and Terengganu. When Tengku Yahya, son of Sultan Ismail, became Sultan of Siak, there was a cup de tat in the Kingdom of Siak, the king fled to Terengganu and died in Dungun. At another time, Tengku Ahmad son of Sultan Zainal Abidin II fled to Riau and married the daughter of the King of Siak named Tengku Puteri by giving a dowry to a country called Dungun